2020
DOI: 10.1186/s43093-020-00028-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grit on voice behavior: mediating role of organizational commitment

Abstract: Employee voice is the voluntary, non-formal and upward communication of ideas, concerns or solutions to work associated problems by an employee. Drawing on conservation of resources theory, our study investigated the direct impact of two antecedents of behavioral outcomes (i.e., grit and organizational commitment) on voice behavior. Moreover, study also examined the mediating influence of organizational commitment in the relationship between grit and voice behavior. Data were collected in two waves time over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 78 publications
3
22
1
Order By: Relevance
“…In this vein, employees who have psychological empowerment have a feeling of control to manage their work and are more likely to get engaged in extra-role behaviors like voice (Spreitzer, 1995). According to Nisar et al (2020), such vital behaviors like raising voice work not only for the betterment of organizations but also for employees as well.…”
Section: Psychological Empowerment As Mediatormentioning
confidence: 99%
“…In this vein, employees who have psychological empowerment have a feeling of control to manage their work and are more likely to get engaged in extra-role behaviors like voice (Spreitzer, 1995). According to Nisar et al (2020), such vital behaviors like raising voice work not only for the betterment of organizations but also for employees as well.…”
Section: Psychological Empowerment As Mediatormentioning
confidence: 99%
“…Organizational commitment refers to the employees’ emotional attachment to the organization [ 18 , 19 ]. Previous studies have explored positive effects of employee prosocial behavior [ 20 ], self-efficacy [ 21 ], and thriving at work [ 22 ] on organizational commitment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study empirically examines the role of managerial support in the relationship between employees’ prosocial motivation and organizational commitment. Bearing the former claims in mind, organizational commitment is a highly researched job attitude in the field of organizational behavior, management [ 19 , 23 ], human resources management [ 24 ], and organizational psychology [ 25 ]. This issue has attracted extensive attention from scholars and practitioners due to its positive organizational and individual outcomes such as higher productivity, job performance [ 26 ], better work-life balance, workplace stability, employee satisfaction [ 27 , 28 ], organizational citizenship behavior, better attendance, employee retention, and lower turnover intention [ 29 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Employees are more likely to exhibit voice behavior when they have a special attachment to their organization [63]. Prior studies found that affective commitment is the strongest indicator of employee voice behavior [23,25]. Therefore, in line with these prior studies and conservation of resource theory, we anticipate that employees will be involved in extra-role behavior (i.e., voice behavior) when they are emotionally attached to their employing organization.…”
Section: Affective Commitment and Voice Behaviormentioning
confidence: 70%
“…By favoring this empirical assumption, our study proposed that affective commitment encourages employee voice behavior. Only those employees exhibit voice behavior who are highly committed to the organization, its goals, and values [24,25]. Employees with increased organizational commitment are extra work oriented as compared to those who are less committed [26].…”
Section: Introductionmentioning
confidence: 99%